2014
DOI: 10.1111/apha.12416
|View full text |Cite
|
Sign up to set email alerts
|

Application of microRNAs in diagnosis and treatment of cardiovascular disease

Abstract: Cardiovascular disease (CVD) is a major cause of morbidity and mortality worldwide. Innovative, more stringent diagnostic and prognostic biomarkers and effective treatment options are needed to lessen its burden. In recent years, microRNAs have emerged as master regulators of gene expression - they bind to complementary sequences within the mRNAs of their target genes and inhibit their expression by either mRNA degradation or translational repression. microRNAs have been implicated in all major cellular proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 175 publications
(188 reference statements)
1
133
0
1
Order By: Relevance
“…miRNAs regulate gene expression by accelerating mRNA degradation or inhibiting translation at the posttranscriptional level by binding the 3'-untranslated region (UTR) of their target mRNAs [4][5][6] . Numerous studies have revealed that some miRNAs play a significant role in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate gene expression by accelerating mRNA degradation or inhibiting translation at the posttranscriptional level by binding the 3'-untranslated region (UTR) of their target mRNAs [4][5][6] . Numerous studies have revealed that some miRNAs play a significant role in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRs) are small, generally noncoding RNAs, that regulate gene expression via post-transcriptional degradation or translational repression [14]. Unquestionably, miRs are fundamental regulators of numerous biological processes.…”
Section: Coding or Noncoding: Whether “Tis Nobler In The Mind To Suffmentioning
confidence: 99%
“…33 Endothelium-specific inactivation of this enzyme is associated with altered expression of vascular endothelial growth factor (VEGF), eNOS, IL-8, and the angiopoietin cell surface receptors Tie-I and Tie-2, compromising endothelial function. 34 In addition, miRNAs also serve as paracrine ligands of the toll-like receptors, an exosome-mediated activity that is independent of post-transcriptional regulatory function. 35 Several miRNAs have been identified to play an important role in regulating endothelial function in normal as well as pathological conditions (Table 1).…”
Section: Microrna and Their Role In Vascular Homeostasismentioning
confidence: 99%